2010
DOI: 10.1021/ja9083946
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Linear−Dendritic Diblock Copolymers: From Nanofibers to Polymersomes

Abstract: We report the formation of cylindrical micelles, sheet-like micelles, tubular micelles, as well as polymer vesicles by a new series of amphiphilic linear-dendritic block-copolymers (BCs). The BCs, noted as PEGm-AZOn, are composed of poly(ethylene glycol) (PEG) chains of different molecular weights as hydrophilic blocks and the first four generations of azobenzene-containing dendrons based on 2,2-bis(hydroxymethyl)propionic acid (bis-MPA) as hydrophobic blocks (m represents the degree of polymerization of PEG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
190
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(204 citation statements)
references
References 100 publications
12
190
1
1
Order By: Relevance
“…A previous study has demonstrated that the size and morphology of the vesicular structures depends on their hydrophobic/hydrophilic ratio [18]. In the case of PEG-AZO2, long nanofibers have been observed, whereas for PEG-AZO4 sheet-like micelles have been reported.…”
Section: High Pressure Transitionmentioning
confidence: 93%
See 1 more Smart Citation
“…A previous study has demonstrated that the size and morphology of the vesicular structures depends on their hydrophobic/hydrophilic ratio [18]. In the case of PEG-AZO2, long nanofibers have been observed, whereas for PEG-AZO4 sheet-like micelles have been reported.…”
Section: High Pressure Transitionmentioning
confidence: 93%
“…The aggregation behavior of PEGAZOn depends on the generation number of the dendritic block; i.e., the hydrophilic/hydrophobic ratio of the LDBC (see Chart 1). Moreover, the photo-responsiveness of the polymeric vesicles was also shown [18].…”
Section: Introductionmentioning
confidence: 97%
“…We have recently reported photo-responsive polymersomes (del Barrio et al 2010) base on amphiphilic PEG-b-azodendron block copolymer with a hydrophobic block based on the fourth generation of aliphatic polyester dendrons functionalized at the periphery with cyanoazobenzene mesogens (PEG45-AZO16). The polymersomes in water were prepared by nanoprecipitation with dioxane/water co-solvents followed by extensive dialyse against water.…”
Section: Systems With Photoactive Groups In Their Polymer Structuresmentioning
confidence: 99%
“…The isotropic blocks are highly immiscible in the liquid crystal (LC) phase, the systems are easily segregated to form microphase-separated morphology [6][7][8][9]. The competition between the LC order and phase-separated confinement can result in a rich variety of morphologies and nanostructures like spheres, cylinders, lamellae phase domains with an increase in volume ratio of the LC blocks [8][9][10][11][12][13][14][15]. The amphiphilic liquid crystalline block copolymers (LCBCs) can also self-assemble in selected solvents to form various polymeric aggregates such as spherical micelles, vesicles and nanotubes, which can be used in drug delivery systems, nanoreactors and others [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%